Comparing mini-sternotomy to full median sternotomy for aortic valve replacement with propensity-matching methods - Liu, Rui; Song, Jiangping; Chu, Junmin; Hu, Shengshou; Wang, Xian-qiang (Frontiers in Surgery, 2022)
Abstract Objective: To compare clinical outcomes between mini-sternotomy and full median sternotomy for aortic valve replacement using propensity-matching methods. Methods: From August 2014 to July 2021, a total of 1445 patients underwent isolated aortic valve surgery, 1247 via full median sternotomy and 198 via mini-sternotomy. To reduce the impact of potential confounding factors, a propensity score based on 19 variables was used to obtain 198 well-matched case pairs, which include 231 aortic valve regurgitations and 165 aortic stenosis cases. Result: Occurrences of in-hospital mortality (P=0.499), stroke (P>0.999), renal failure (P=0.760), and paravalvular leakage (P= 0.224) were similar between two groups. No significant difference of operation, CPB, and aortic cross-clamp times are found between two groups. However, compared with full sternotomy group, mini-sternotomy group has less postoperative 24-hour drainage (131.7±82.8 ml, p<0.001), and total drainage (459.3±306.3 ml, p<0.001). The median mechanical ventilation time was 9.4(IQR5.4-15.6) and 9.8(IQR6.1-14.4) in mini-sternotomy and full sternotomy groups (P=0.284). There are no significant differences of intensive care unit stay, and postoperative stay between two groups. For either aortic valve regurgitations or aortic stenosis patients, significantly less postoperative 24-hour and total drainage are still found in mini-sternotomy group compared with full sternotomy group. Conclusions: Mini-sternotomy for aortic valve replacement is a safe procedure, with not only cosmetic advantages but less postoperative drainage compared with full sternotomy. Mini-sternotomy should be considered for most aortic valve operations.